2011
DOI: 10.1080/15504263.2011.569192
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Sociodemographic Correlates of Mental Health Problems Among Emergency Department Patients With High-Risk and Dependent Alcohol Use Patterns

Abstract: Results suggest that emergency department patients with high-risk drinking patterns experience high rates of depression, anxiety, and cognitive function problems. Vulnerable groups may be identified based on sociodemographic characteristics. Incorporating standardized screening for mental health problems in the emergency department may be appropriate, especially among those presenting with alcohol-related problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The aim of this study, then, was to determine whether treatment participation rate mediated the relationships between three baseline issue severities and post-treatment employment status, that is, whether some of the increased employment after treatment in consumers with higher baseline levels of alcohol use, drug use, and psychiatric issue severity could be attributed to a higher treatment participation rate. Support for this relationship came from prior studies of individuals with SUDs and psychiatric disorders, which suggested that (a) those with lower baseline substance use or psychiatric issue levels are more likely to show a higher treatment participation rate (Drapalski, Bennett, & Bellack, 2011;Evans et al, 2009;Neighbors, Barnett, Rohsenow, Colby, & Monti, 2010), (b) those with a higher treatment participation rate are more likely to be employed after treatment (Evans et al, 2009;Funn & Woodruff, 2011), and (c) those with lower baseline substance use or psychiatric issues are more likely to be employed (Bond, Drake, & Becker, 2012;Hogue, Dauber, Dasaro, & Morgenstern, 2010). Based on this research, then, we hypothesized that treatment participation rate would mediate the relationships between each of the three baseline issue severities and employment status at 210 days after intake into a long-term outpatient substance abuse program.…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this study, then, was to determine whether treatment participation rate mediated the relationships between three baseline issue severities and post-treatment employment status, that is, whether some of the increased employment after treatment in consumers with higher baseline levels of alcohol use, drug use, and psychiatric issue severity could be attributed to a higher treatment participation rate. Support for this relationship came from prior studies of individuals with SUDs and psychiatric disorders, which suggested that (a) those with lower baseline substance use or psychiatric issue levels are more likely to show a higher treatment participation rate (Drapalski, Bennett, & Bellack, 2011;Evans et al, 2009;Neighbors, Barnett, Rohsenow, Colby, & Monti, 2010), (b) those with a higher treatment participation rate are more likely to be employed after treatment (Evans et al, 2009;Funn & Woodruff, 2011), and (c) those with lower baseline substance use or psychiatric issues are more likely to be employed (Bond, Drake, & Becker, 2012;Hogue, Dauber, Dasaro, & Morgenstern, 2010). Based on this research, then, we hypothesized that treatment participation rate would mediate the relationships between each of the three baseline issue severities and employment status at 210 days after intake into a long-term outpatient substance abuse program.…”
Section: Hypothesesmentioning
confidence: 99%
“…In conclusion, many studies exploring relationships between these five critical variables have shown evidence for (a) positive relationships between SUD and psychiatric issue severity levels (Latkin, Curry, Hua, & Davey, 2007), (b) positive relationship between treatment participation rate and treatment outcomes (Hatzenbuehler et al, 2011;Neumann & Hare, 2008), and (c) negative relationships between issue severity levels and employment status (Evans, Li, & Hser, 2009;Funn & Woodruff, 2011).…”
mentioning
confidence: 95%
“…Literature included in the current review noted that individuals who experience psychological or mental health issues, or those who have health conditions exacerbated by mental health concerns, often present to ED for assessment and support ( The emergency department is a focal point of contact for many vulnerable individuals and those of sub-groups who may require specific support, such as young people in out-of-home care, with suicidal ideation (Cronholm et al, 2010), or people from certain racial and ethnic minorities (Wells et al, 2013). Mental health presentations to ED are often complex, in conjunction with other factors and may include situational crises such as homelessness and substance misuse (Funn & Woodruff, 2011), and therefore require deliberate psychosocial attention.…”
Section: Key Practice Area -Mental Healthmentioning
confidence: 99%
“…As reflected above, a core theme across the reviewed literature is that people in psychological distress often present at ED in crisis (Baraff et al, 2006). Emergency departments are a focal point through which to reach some people with depression and anxiety (Funn & Woodruff, 2011), and those of some ethnic communities who experience distress (Wells et al, 2013).…”
Section: Key Practice Area -Suicide Risk and Crisismentioning
confidence: 99%
See 1 more Smart Citation